The Use of Digital Elevation Models (DEMs) for Bathymetry Development in Large Tropical Reservoirs - Anda, José de; Rangel-Peraza, Jesus Gabriel; Obregon, Oliver; Nelson, James; Williams, Gustavious P.; Jarquín-Javier, Yazmín; Miller, Jerry; Rode, Michael (IntechOpen, 2012)
None